2015
DOI: 10.1037/a0038155
|View full text |Cite
|
Sign up to set email alerts
|

Group motivational interviewing for adolescents: Change talk and alcohol and marijuana outcomes.

Abstract: Objective Little is known about what may distinguish effective and ineffective group interventions. Group motivational interviewing (MI) is a promising intervention for adolescent alcohol and other drug (AOD) use; however, the mechanisms of change for group MI are unknown. One potential mechanism is change talk, which is client speech arguing for change. The present study describes the group process in adolescent group MI and effects of group-level change talk on individual alcohol and marijuana outcomes. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
130
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(149 citation statements)
references
References 80 publications
11
130
3
Order By: Relevance
“…A study of a group MI intervention for adolescents found that open questions and reflections of change talk were more likely than change to be followed by change talk, that reflections of sustain talk tended to suppress subsequent change talk, and that change talk by group members was more likely than chance to be followed by more change talk. This situation is not directly comparable to individual counseling since the previous “client state” may not have been produced by the same person who makes the next client utterance, but does reinforce that it may be important to distinguish among MI consistent therapist behaviors and to account for the context in which they appear (D'Amico et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…A study of a group MI intervention for adolescents found that open questions and reflections of change talk were more likely than change to be followed by change talk, that reflections of sustain talk tended to suppress subsequent change talk, and that change talk by group members was more likely than chance to be followed by more change talk. This situation is not directly comparable to individual counseling since the previous “client state” may not have been produced by the same person who makes the next client utterance, but does reinforce that it may be important to distinguish among MI consistent therapist behaviors and to account for the context in which they appear (D'Amico et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…For example, in our intervention work with adolescents who have a first time drug or alcohol offense, one of the sessions involves discussing how marijuana use can change the brain and affect memory and concentration (D’Amico, Hunter, Miles, Ewing, & Osilla, 2013). We found that addressing questions and discussing this type of information in a nonjudgmental way in the adolescent group setting can increase change talk, or talk that argues for decreasing marijuana use (D’Amico, et al, 2015). This is important because change talk among both adults and adolescents is typically associated with subsequent decreases in substance use (Magill, Apodaca, Barnett, & Monti, 2010; Walker, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A recent focus group study with at-risk youth found that most of these youth perceived marijuana use as “normal,” with 90% voicing positive attitudes toward marijuana use (Sanders, 2012). Similarly, youth with a first time alcohol or marijuana offense viewed using marijuana as less risky than drinking, and they also associated marijuana use with fewer negative consequences compared to drinking (D’Amico, et al, 2015). …”
mentioning
confidence: 99%
“…Given that perceptions of harmfulness and disapproval of marijuana are declining, 2 and youth view marijuana use as less dangerous than drinking, 45 we must begin to address how changing views of marijuana might increase risk for not only marijuana use, but other behaviors such as DUI/RWDD of marijuana. 46 Additionally past month alcohol use and perceived peer use of alcohol predicted DUI/RWDD.…”
Section: Discussionmentioning
confidence: 99%